The vote collectors : the true story of the scamsters, politicians, and preachers behind the nation's greatest electoral fraud - Graff, Michael (Journalist); Ochsner, Nick (The University of North Carolina Press, 2021)
"In November 2018, Baptist preacher Mark Harris beat the odds, narrowly fending off a blue wave in the sprawling Ninth District of North Carolina. But word soon got around that something fishy was going on in rural Bladen County. At the center of the mess was a local political operative named McCrae Dowless. Dowless had learned the ins and outs of the absentee ballot system from Democrats before switching over to the Republican Party. Bladen County's vote-collecting cottage industry made national headlines, led to multiple election fraud indictments, toppled North Carolina GOP leadership, and left hundreds of thousands of North Carolinians without congressional representation for nearly a year. In The Vote Collectors, Michael Graff and Nick Ochsner tell the story of the political shenanigans in Bladen County, exposing the shocking vulnerability of local elections and explaining why our present systems are powerless to monitor and prevent fraud. In their hands, this tale of rural corruption becomes a fascinating narrative of the long clash of racism and electioneering-and a larger story about the challenges to democracy in the rural South. At a time rife with accusations of election fraud, The Vote Collectors shows the reality of election stealing in one southern county, where democracy was undermined the old-fashioned way: one absentee ballot at a time"--